Metabolic control of induced pluripotency - Sinenko, Sergey A.; Tomilin, Alexey N. (Frontiers in Cell and Developmental Biology, 2024)
Pluripotent stem cells of the mammalian epiblast and their cultured counterparts—embryonic stem cells (ESCs) and epiblast stem cells (EpiSCs)—have the capacity to differentiate in all cell types of adult organisms. An artificial process of reactivation of the pluripotency program in terminally differentiated cells was established in 2006, which allowed for the generation of induced pluripotent stem cells (iPSCs). This iPSC technology has become an invaluable tool in investigating the molecular mechanisms of human diseases and therapeutic drug development, and it also holds tremendous promise for iPSC applications in regenerative medicine. Since the process of induced reprogramming of differentiated cells to a pluripotent state was discovered, many questions about the molecular mechanisms involved in this process have been clarified. Studies conducted over the past 2 decades have established that metabolic pathways and retrograde mitochondrial signals are involved in the regulation of various aspects of stem cell biology, including differentiation, pluripotency acquisition, and maintenance. During the reprogramming process, cells undergo major transformations, progressing through three distinct stages that are regulated by different signaling pathways, transcription factor networks, and inputs from metabolic pathways. Among the main metabolic features of this process, representing a switch from the dominance of oxidative phosphorylation to aerobic glycolysis and anabolic processes, are many critical stage-specific metabolic signals that control the path of differentiated cells toward a pluripotent state. In this review, we discuss the achievements in the current understanding of the molecular mechanisms of processes controlled by metabolic pathways, and vice versa, during the reprogramming process.